Demonstration by Infra-Red Imaging of a Temperature Control Defect in a Decompression Sickness Model Testing Minocycline - Desruelle, Anne-Virginie; Louge, Pierre; Richard, Simone; Blatteau, Jean-Eric; Gaillard, Sandrine; De Maistre, Sébastien; David, Hélène; Risso, Jean-Jacques; Vallée, Nicolas (Frontiers in Physiology, 2019)
The prevention, prognosis and resolution of decompression sickness (DCS) are not satisfactory. The aetiology of DCS has highlighted thrombotic and inflammatory phenomena that could cause severe neurological disorders or even death. Given the immunomodulatory effects described for minocycline, an antibiotic in widespread use, we have decided to explore its effects in an experimental model for decompression sickness. 40 control mice (Ctrl) and 40 mice treated orally with 90 mg/kg of minocycline (MINO) were subjected to a protocol in a hyperbaric chamber, compressed with air. The purpose was to mimic a scuba dive to a depth of 90 m and its pathogenic decompression phase. Clinical examinations and blood counts were conducted after the return to the surface. For the first time they were completed by a simple infrared (IR) imaging technique in order to assess feasibility and its clinical advantage in differentiating the sick mice (DCS) from the healthy mice (NoDCS). In this tudy, exposure to the hyperbaric protocol provoked a reduction in the number of circulating leukocytes. DCS in mice, manifesting itself by paralysis or convulsion for example, is also associated with a fall in platelets count. Cold areas (<25°C) were detected by IR in the hind paws and tail with significant differences (p<0.05) between DCS and NoDCS. Severe hypothermia was also shown in the DCS mice. The ROC analysis of the thermograms has made it possible to determine that an average tail temperature below 27.5°C allows us to consider the animals to be suffering from DCS (OR=8; AUC=0.754, p=0.0018). Minocycline modulates blood analysis and it seems to limit the mobilization of monocytes and granulocytes after the provocative dive. While a higher proportion of mice treated with minocycline experimented DCS symptoms, there is no significant difference. The infrared imaging has made it possible to show severe hypothermia. It suggests an alteration of thermogenesis in DCS animals. Surveillance by infrared camera is fast and it can aid the prognosis in the case of decompression sickness in mice.